Penyuluhan tentang Perawatan Pasca Persalinan untuk Meningkatkan Kesehatan Ibu Postpartum - Asikin, Siti Badria (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The postpartum period is a crucial period in a mother's life because it is closely related to physical and psychological recovery, and adaptation to the new role of mother. However, lack of knowledge regarding postpartum care remains a major problem, increasing the risk of complications such as bleeding, infection, lactation disorders, and postpartum depression. This community service activity aims to provide education on the importance of postpartum care to improve the health of postpartum mothers. The methods used were health education through lectures, discussions, and the distribution of leaflets to postpartum mothers and their families. The results of the activity showed an increase in participants' understanding of postpartum danger signs, maternal nutrition, breast care, reproductive organ care, and psychological support. Thus, this education activity can increase awareness and health practices of postpartum mothers, thereby supporting an optimal recovery process.